Determinant: Follow-up of Audit Result Recommendations on the Quality of Regional Government Financial Reports: Empirical Study Regional Government-LKPD Period 2015-2019 - Pramiudi, Udi (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine the Follow-up of Recommendations for Examination Results, the Quality of Financial Statements and the Effect of Follow-up Recommendations on the Quality of Financial Statements. This research was conducted at the Regional Government-LKPD for the 2015-2019 period.This study used a quantitative approach with descriptive design and associative research. The research data used the technical census of 542 LKPD for the 2015-2019 period. Data analysis using binary logistic regression analysis. The results showed that in the 2015-2019 period local governments had followed up on the Examination Results Recommendations according to the recommendations by 61.6%, followed up but not according to the recommendations by 30.5%, had not followed up by 7.8%, and could not follow up by 0.1%. Furthermore, in the same period 100% WTP opinion has been achieved by all provincial governments, in district governments it reaches 88%, while in city governments it reaches 94%. The results showed that the Follow-up Recommendation of the Examination Results had a positive effect on the quality of the Local Government's financial statements. Thus, it means that follow-up recommendations on audit results can improve the quality of financial statements, if local governments follow up on the recommendations given by auditors, it will be able to improve the quality of financial statements for the next period. Keywords : Follow-up Recommendations of Examination Results, Quality of Financial Statements